2009
DOI: 10.1021/om9008229
|View full text |Cite
|
Sign up to set email alerts
|

User-Friendly Precatalyst for the Methylation of Polyfluoroaryl Imines

Abstract: A readily accessible, user-friendly Pt(II) complex (Cl2Pt(SMe2)2, 2) shows good reactivity for selective, catalytic methylation of polyfluoroarylimines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 51 publications
1
41
0
Order By: Relevance
“…Catalytic cross-coupling reactions of 2,3,5,6-tetrafluoropyridine. [4,14,17,21,[23][24][25][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]51,70]. Chambers and Sandford described palladium catalysed Suzuki cross-coupling reactions via C-Br activation of 2,4,6-tribromo-3,5-difluoropyridine and aromatic boronic acids.…”
Section: Bondmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalytic cross-coupling reactions of 2,3,5,6-tetrafluoropyridine. [4,14,17,21,[23][24][25][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]51,70]. Chambers and Sandford described palladium catalysed Suzuki cross-coupling reactions via C-Br activation of 2,4,6-tribromo-3,5-difluoropyridine and aromatic boronic acids.…”
Section: Bondmentioning
confidence: 99%
“…Thus, hydrodefluorination or cross coupling reactions can provide fluorinated building blocks, which are often not accessible otherwise . However, catalytic C-F bond functionalization reactions of highly fluorinated aromatic precursors via cross coupling reactions are still rare [4,14,17,[23][24][25][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. Radius et al reported an initial and exceptional example of a nickelmediated Suzuki-Miyaura cross coupling reaction of perfluorotoluene with aryl boronic acids on using a nickel(II) carbene complex as catalyst [25].…”
Section: Introductionmentioning
confidence: 99%
“…Much of this recent activity is driven by the need for synthetic procedures to incorporate fluorine or a CF 3 group strategically in the synthesis of pharmaceuticals or PET reagents, leading to the development of new methodology for formation of C-F and C-CF 3 bonds [110][111][112][113][114][115][116][117][118][119][120][121][122]. Organometallic chemistry involving the chemical functionalization of C-F bonds also continues to be an active field [123][124][125][126][127][128][129][130][131][132][133][134][135][136].…”
Section: [ ( S C H E M E _ 4 ) T D $ F I G ]mentioning
confidence: 99%
“…The procedure is highly selective as illustrated by the coupling of 453 that leaves the weaker carbon-bromine bond intact. The air-stable Pt(II) precatalyst Cl 2 Pt(SMe 2 ) 2 represents a more practical alternative for this chemistry but shows slightly lower efficiency [308].…”
Section: Platinum-catalyzed Cross-coupling Reactionsmentioning
confidence: 99%